2014
DOI: 10.1002/ijc.29324
|View full text |Cite
|
Sign up to set email alerts
|

Combined evaluation of a panel of protein and miRNA serum‐exosome biomarkers for pancreatic cancer diagnosis increases sensitivity and specificity

Abstract: Late diagnosis contributes to pancreatic cancer (PaCa) dismal prognosis, urging for reliable, early detection. Serum-exosome protein and/or miRNA markers might be suitable candidates, which we controlled for patients with PaCa. Protein markers were selected according to expression in exosomes of PaCa cell line culture supernatants, but not healthy donors' serumexosomes. miRNA was selected according to abundant recovery in microarrays of patients with PaCa, but not healthy donors' serum-exosomes and exosome-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
296
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(319 citation statements)
references
References 51 publications
11
296
1
1
Order By: Relevance
“…Intensification of miRNA expression signals has been reported in several recent studies. [73][74][75] However, the exosomal intensification effect on protein biomarkers was not as significant as its effect on miRNAs in this study. Further study is needed on the mechanism of miRNA and protein compartmentation into exosomes to explain the significant reduction of signal intensification of proteins compared to that of miRNAs.…”
Section: Discussioncontrasting
confidence: 74%
“…Intensification of miRNA expression signals has been reported in several recent studies. [73][74][75] However, the exosomal intensification effect on protein biomarkers was not as significant as its effect on miRNAs in this study. Further study is needed on the mechanism of miRNA and protein compartmentation into exosomes to explain the significant reduction of signal intensification of proteins compared to that of miRNAs.…”
Section: Discussioncontrasting
confidence: 74%
“…Both types of EV therefore carry, in their membranes or in their soluble fractions, some characteristics of the plasma membrane of the cell from which they originate. An in depth description is beyond the scope of the current review, however, an example of this in cancer is the transmembrane molecule CD44v6 expressed on metastasizing cancer cells [43,64,65]. In the case of pancreatic adenocarcinoma, CD44v6 carried by tumor exosomes in their soluble matrix appears to play a role in premetastatic niche preparation by modulating cells of the organ in provision for tumor cell arrival and embedding [44,64].…”
Section: Tumor Exosomesmentioning
confidence: 99%
“…Importantly, miRNAs can be readily detected in small-volume samples using specific and sensitive quantitative real-time PCR (qRT-PCR) (68). Additionally, EV-associated miRNAs have been used as diagnostic and prognostic markers (20,(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79). Microarray analyses of miRNAs in EV-enriched fractions of serum from 88 patients with primary colorectal cancer (CRC) and 11 healthy controls revealed that that the levels of 7 miRNAs were significantly higher in the serum EVs of CRC patients compared with serum EVs from healthy donors (74).…”
Section: The Emerging Role Of Evs In Cancer Immunologymentioning
confidence: 99%